1997
DOI: 10.1182/blood.v89.5.1635
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Inducible Virus in CD45RA Naive Cells After Human Immunodeficiency Virus-1 Entry Accounts for Preferential Viral Replication in CD45RO Memory Cells

Abstract: Controversy exists concerning the preferential infection and replication of human immunodeficiency virus-1 (HIV-1) within naive (CD45RA+) and memory (CD45RO+) subsets of CD4+ lymphocytes. To explore the susceptibility of these subsets to HIV-1 infection, we purified CD45RA+/CD4+ (RA) and CD45RO+/CD4+ (RO) cells from normal donors and subjected them to a novel monokine activation culture scheme. Following HIV-1 infection and interleukin-2 (IL-2) induction, viral production measured on day 13 was 19-fold greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 31 publications
5
22
0
Order By: Relevance
“…Thus, the localization of the immunosuppressive motif in FP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] suggests that the APC/T cell physical interaction is exploited by the virus to simultaneously invade the T cell and interfere with T cell activation. Taken together with the fact that HIV pref-erentially infects HIV specific T cells (29 -32), our observations might explain the unsolved puzzle of decreased HIV-specific T cell immunity amid general T cell hyperactivation observed in HIV-infected patients in the early stages of the infection (33,34). Other immunosuppressive activities described for HIV might collaborate in the takeover of the immune response that finally leads to the collapse of the host's immune system (25,35).…”
Section: Discussionmentioning
confidence: 57%
“…Thus, the localization of the immunosuppressive motif in FP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] suggests that the APC/T cell physical interaction is exploited by the virus to simultaneously invade the T cell and interfere with T cell activation. Taken together with the fact that HIV pref-erentially infects HIV specific T cells (29 -32), our observations might explain the unsolved puzzle of decreased HIV-specific T cell immunity amid general T cell hyperactivation observed in HIV-infected patients in the early stages of the infection (33,34). Other immunosuppressive activities described for HIV might collaborate in the takeover of the immune response that finally leads to the collapse of the host's immune system (25,35).…”
Section: Discussionmentioning
confidence: 57%
“…Notably, CXCR4 is mainly expressed on naive CD4 + T lymphocytes (CD45RA), while CCR5 is predominantly expressed on memory CD4 + T lymphocytes (CD45RO) [8]. Some studies have suggested that the differentiation of human CD4 + T cells toward a memory phenotype is associated with an increased susceptibility to HIV-1 infection [11][12][13][14]. Notably, most of human intestinal lamina propria lymphocytes (LPL) are memory T cells and are in a peculiar "activation state" [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Controversy goes on regarding the susceptibility of RA and RO cells to HIV and whether these subsets are lost or functionally altered in the course of HIV-1 infection. Several cross-sectional and longitudinal studies investigating CD4 subsets in HIV + individuals detected a decline in CD4RA lymphocytes that correlates with the progression of disease [21][22][23][24][25]. These findings reveal that the loss of naive cells begins relatively early after infection, when the infected individuals are otherwise asymptomatic and still have substantial levels of CD4 T cells, and involves both CD4 and CD8 subsets.…”
Section: Discussionmentioning
confidence: 81%
“…In this context, recent findings also show a preferential decline in naive T cell numbers that correlates with progression of HIV disease and with disruption of the T cell repertoire [24]. In vitro studies indicate that CD4CD45RA and RO populations display a comparable susceptibility to HIV-1 entry and to virus replication [25,26]. However, only infected memory cells undergo apoptosis upon mitogen stimulation, suggesting a differential sensitivity of the RA and RO subset to HIV-1 infection [26].…”
Section: Introductionmentioning
confidence: 94%